A New Silicon Drift Detector for High Spatial Resolution STEM-XEDS: Performance and Applications. (29th July 2014) - Phillips, Patrick J.; Paulauskas, Tadas; Rowlands, Neil; Nicholls, Alan W.; Low, Ke-Bin; Bhadare, Santokh; Klie, Robert F.
Abstract A newly designed, 100 mm2, silicon drift detector has been installed on an aberration-corrected scanning transmission electron microscope equipped with an ultra-high resolution pole piece, without requiring column modifications. With its unique, windowless design, the detector's active region is in close proximity to the sample, resulting in a dramatic increase in count rate, while demonstrating an increased sensitivity to low energy X-rays and a muted tilt dependence. Numerous examples of X-ray energy dispersive spectrometry are presented on relevant materials such as AlxGa1−xN nanowires, perovskite oxides, and polycrystalline CdTe thin films, across both varying length scales and accelerating voltages.